Regions of bone metastasis visualised in whole-body bone scanning - Balci, T. A.; Uzar, E.; Demirel, B. B.; Tasdemir, B. (Springer, 2007)
[Abstract Not Available]
20th Annual Congress of the European-Association-of-Nuclear-Medicine -- 2007 -- Copenhagen, DENMARK